METAPHORICAL EXPRESSIONS OF BANANA NAMES IN JAVANESE LANGUAGE - Hidayah, Arini; I Dewa Putu Wijana; Hendrokumoro (Acceleration: Multidisciplinary Research Journal, 2025)
Plant naming in Javanese culture is not merely descriptive but is laden with metaphorical meaning that reflects cultural values and collective cognition. This study aims to uncover the cognitive processes behind the use of metaphors in the names of banana varieties (gêdhang) in the Javanese language. The research method employed is descriptive qualitative, with data collected through documentation of the Javanese dictionary, observation, and interviews with local informants. Data analysis was conducted using a referential approach and a reflective-introspective method to identify the source domains, target domains, and conceptual structure of the metaphors. The results show that the metaphors in banana names take the form of idiomatic phrases, with loci based on construction attributes. Source domains include place, beauty, small things, position, and spirit beings, while target domains involve flavor, color, texture, seeds, and the number of fruits. The discussion highlights how language reflects local wisdom and cultural values, and how metaphors function conceptually in organizing human experiences. This study enriches conceptual metaphor theory and opens avenues for further exploration in other ethnobotanical lexicons.